2011
DOI: 10.1364/oe.20.000256
|View full text |Cite
|
Sign up to set email alerts
|

The role of chiral local field enhancements below the resolution limit of Second Harmonic Generation microscopy

Abstract: Abstract:While it has been demonstrated that, above its resolution limit, Second Harmonic Generation (SHG) microscopy can map chiral local field enhancements, below that limit, structural defects were found to play a major role. Here we show that, even below the resolution limit, the contributions from chiral local field enhancements to the SHG signal can dominate over those by structural defects. We report highly homogeneous SHG micrographs of star-shaped gold nanostructures, where the SHG circular dichroism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 51 publications
(54 reference statements)
2
38
1
Order By: Relevance
“…The generated heat can go beyond the melting point and finally decorates the optical response of the structure. Similar simulation-experiment comparisoncan be found in [26][27][28][29][30][31].…”
Section: Volume Integral Equation Formulation and Volumetric Methods Osupporting
confidence: 79%
“…The generated heat can go beyond the melting point and finally decorates the optical response of the structure. Similar simulation-experiment comparisoncan be found in [26][27][28][29][30][31].…”
Section: Volume Integral Equation Formulation and Volumetric Methods Osupporting
confidence: 79%
“…[139][140][141][142] For example, the chirality of plasmonic excitations on gold nanostructures was studied based on a farfield second-harmonic imaging method with circularly polarised light (Fig. 16).…”
Section: Methods Of Near-field Measurements Of Local Optical Activitymentioning
confidence: 99%
“…23,25,27 Previous research demonstrated the enhanced spatial resolution for both SHG and TPL imaging because of their nonlinear dependence upon the excitation power, 38,39 while the resolution of linear scattering was restricted to the diffraction limit. 40 To determine the spatial resolution of this multimodal optical microscopy experimentally, the gold nanorods were imaged by SHG, TPL, and RLS, respectively.…”
Section: Spatial Resolution Of Multimodal Optical Microscopymentioning
confidence: 99%
“…Notably, the resolutions of SHG, TPL, and RLS were comparable to or even much higher than those reported in the previous researches. 23,38,43 For example, the resolution of SHG was 200 nm for the imaging of star-shaped golds, 38 the resolution of TPL was 300 nm for the imaging of blood vessels, 23 and the Rayleigh scattering displayed submicrometer resolution for the imaging of single-walled carbon nanotubes. 43 The high spatial resolution of this multimodal optical microscopy offered great promise for further applications in biological and biomedical research.…”
Section: Spatial Resolution Of Multimodal Optical Microscopymentioning
confidence: 99%